Cities as spatial clusters - Rauch, Ferdinand (Journal of economic geography, 2014)
This article shows that Zipf’s Law for cities can emerge as a property of a clustering process. If initially uniformly distributed people chose their location based on a specific gravity equation as found in trade studies, they will form cities that follow Zipf’s Law in expected value. This view of cities as spatial agglomerations is supported empirically by the observation that larger cities are surrounded by larger hinterland areas and larger countryside populations.